Defective suppression in the autologous mixed lymphocyte reaction in patients with Crohn's disease - KELLEHER, DERMOT P (BMJ, 1989)
T helper and suppressor cell control of autologous immunoglobulin production was measured in 14 patients with Crohn's disease (CD) using autologous B cells or monocytes to stimulate regulatory T-cell activity. A pronounced defect in suppressor cell function was observed in the patient group but not in matched controls irrespective of whether B cells or monocytes were used as the stimulus. This defect was observed for IgG, A and M. This defect was seen both in patients with active disease and with inactive CD suggesting the possibility that a primary regulatory defect might exist in this disease. The patient group displayed normal helper cell function.
PUBLISHED
Keywords: Clinical Medicine